2005
DOI: 10.1590/s0037-86822005000300001
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of 151 patients with cutaneous leishmaniasis treated with meglumine antimoniate

Abstract: We retrospectively analyzed a series of 151 cases of cutaneous leishmaniasis treated between 1967 and 1982. One-hundred-and-thirty-nine (92%) patients presented with active lesions and were treated with daily doses of meglumine antimoniate: 81 adults received a 5-ml vial IM and 58 children received 1 to 5ml. Forty-five (32.4%) patients underwent continuous treatment with meglumine antimoniate for 25 to 116 days without rest intervals, and 94 (67.6%) intermittent treatment with 2 to 5 series of meglumine antimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 28 publications
1
17
2
4
Order By: Relevance
“…One patient had no description of lesion site. These results were in disagreement with those of Schubach and others 9 in IL TTM, and Marsden and others 10 in IM TTM. Among eight patients with lesions in lower limbs, seven (87.5%) healed exclusively with IL TTM; and five (62.5%) did not reactivate the lesions.…”
contrasting
confidence: 82%
“…One patient had no description of lesion site. These results were in disagreement with those of Schubach and others 9 in IL TTM, and Marsden and others 10 in IM TTM. Among eight patients with lesions in lower limbs, seven (87.5%) healed exclusively with IL TTM; and five (62.5%) did not reactivate the lesions.…”
contrasting
confidence: 82%
“…[5][6][7][8][9] At the Laboratory of Leishmaniasis Surveillance, Evandro Chagas Clinical Research Institute, Oswaldo Cruz Foundation, Rio de Janeiro, Brazil, we have found continuous or intermittent intramuscular administration of meglumine antimoniate at a dose of 5 mg/kg/day to be effective and well tolerated. [10][11][12][13][14][15] The main side effects of treatment with pentavalent antimonials are myalgia, arthralgia, electrocardiographic Q-T interval prolongation, renal failure and pancreatitis accompanied by elevated lipase levels, among others. 7,11,13,16,17 Older individuals are more affected by mucosal leishmaniasis and also more prone to the side effects of treatment, 13 in addition to presenting other risk factors for the occurrence of dizziness.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, one of the patients who did not achieve cure was submitted to the conventional high dose therapy and had to be hospitalized to treat severe arthralgias. It was noticeable that cure was achieved with a much smaller dose than that recommended by the WHO, at least in Rio de Janeiro State 8 . It also seems evident that this goal was achieved due to the prolongation of the administration period.…”
Section: Discussionmentioning
confidence: 92%